2015
DOI: 10.1002/csr.1373
|View full text |Cite
|
Sign up to set email alerts
|

A Strategic Approach to CSR Communication: Examining the Impact of Brand Familiarity on Consumer Responses

Abstract: Despite the widely acknowledged importance of corporate social responsibility (CSR) communications, our knowledge is limited with regard to various factors affecting consumer responses to such communication efforts. This paper aims to identify the extent to which prior brand familiarity influences consumer responses to CSR communications through a controlled experiment, exploring whether the use of different communication functions for environmental domain of CSR (i.e., publicity and advertising) generates any… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
41
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 91 publications
(133 reference statements)
2
41
0
1
Order By: Relevance
“…the result is similar to the study carried out by Türkel, Uzunoğlu, Kaplan, and Vural (2016). and connects the CSR awareness and purchase intention; the study has found that brand image acts as an intervening variable, the results are significant (t = 6.56), and the H5 was accepted.…”
Section: Conclusion and Discussionsupporting
confidence: 85%
“…the result is similar to the study carried out by Türkel, Uzunoğlu, Kaplan, and Vural (2016). and connects the CSR awareness and purchase intention; the study has found that brand image acts as an intervening variable, the results are significant (t = 6.56), and the H5 was accepted.…”
Section: Conclusion and Discussionsupporting
confidence: 85%
“…Recently, the CSR literature has focused on verifying relevant findings worldwide, since the adoption of such practices has been acknowledged as a decisive factor in generating profits (Arrive & Feng, ; Muttakin & Khan, ; Vogel, ; Waheed & Yang, ). Many researchers have suggested CSR as a key driver of organizational performance, including financial performance, environmental, social, sales, and overall performance (Ağan, Kuzey, Acar, & Açıkgöz, ; Beck, Frost, & Jones, ; De Bakker et al, ; Khan et al, ; Rasheed, Arshed, Malik, & Mahmood, ; Türkel et al, ; Waheed & Yang, ; Yang & Baasandorj, ).…”
Section: Conceptual Background and Research Frameworkmentioning
confidence: 99%
“…Achabou and Dekhili () highlight the need for further research so as to better understand the issue of responsibility in the case of luxury goods. This research focuses in particular on the issue of communication where our knowledge is still limited (Türkel et al ., ).…”
Section: Introductionmentioning
confidence: 97%